ANALISIS PROSES BERPIKIR SPASIAL SISWA DALAM MENYELESAIKAN PERMASALAHAN GEOMETRI DENGAN KONTEKS BUDAYA MASJID AGUNG DEMAK - Nadia Nur Padmasari; Muhtarom Muhtarom; Lukman Harun (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
This research is motivated by the low spatial thinking ability of junior high school students in geometry, especially in visualizing three-dimensional objects and mental manipulation. The focus of the problem is directed at an in-depth analysis of students' spatial thinking processes when solving geometry problems based on the cultural context of the Great Mosque of Demak in terms of Van Hiele's theory. The research method applied is descriptive qualitative through purposive sampling of students who have been previously categorized. The research stages include a geometry ability test on twenty-one students, working on culture-based problems, and semi-structured interview observations. The identification results show eight students with low abilities, eleven with medium abilities, and two with high abilities. The findings reveal significant variations at each cognitive level. Low-ability students were only able to reach the basic visualization stage and experienced obstacles in the aspects of relations and transformation. Medium-ability students showed adequate mastery of visualization and orientation, but were not optimal in reasoning and reflection. In contrast, high-ability students managed to master all spatial indicators comprehensively and optimally. These findings confirm that the level of Van Hiele's geometry ability has a crucial influence on the development of spatial thinking processes in the context of local ethnomathematics. The main conclusion is that the integration of cultural context is able to reveal the depth of mental representation, so that geometric ability becomes the main predictor of success in solving spatial problems logically through a deep and measurable cultural approach in secondary schools. ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya kemampuan berpikir spasial siswa SMP dalam geometri, khususnya dalam memvisualisikan objek tiga dimensi dan manipulasi mental. Fokus masalah diarahkan pada analisis mendalam proses berpikir spasial siswa saat menyelesaikan soal geometri berbasis konteks budaya Masjid Agung Demak ditinjau dari teori Van Hiele. Metode penelitian yang diterapkan adalah kualitatif deskriptif melalui purposive sampling terhadap siswa yang telah dikategorikan sebelumnya. Tahapan penelitian meliputi tes kemampuan geometri terhadap dua puluh satu siswa, pengerjaan masalah berbasis budaya, serta observasi wawancara semiterstruktur. Hasil identifikasi menunjukkan delapan siswa berkemampuan rendah, sebelas sedang, dan dua berkemampuan tinggi. Temuan mengungkapkan variasi signifikan pada setiap tingkatan kognitif. Siswa berkemampuan rendah hanya mampu mencapai tahap visualisasi dasar dan mengalami hambatan aspek relasi serta transformasi. Siswa berkemampuan sedang menunjukkan penguasaan visualisasi dan orientasi memadai, namun belum optimal dalam penalaran dan refleksi. Sebaliknya, siswa berkemampuan tinggi berhasil menguasai seluruh indikator spasial secara menyeluruh dan optimal. Temuan ini menegaskan tingkat kemampuan geometri Van Hiele memiliki pengaruh krusial terhadap perkembangan proses berpikir spasial dalam konteks etnomatematika lokal. Simpulan utamanya adalah integrasi konteks budaya mampu mengungkap kedalaman representasi mental, sehingga kemampuan geometri menjadi prediktor utama keberhasilan menyelesaikan masalah ruang secara logis melalui pendekatan budaya yang mendalam dan terukur di sekolah menengah.